A Novel Mechanism of Endoplasmic Reticulum Stress‐ and c‐Myc‐Degradation‐Mediated Therapeutic Benefits of Antineurokinin‐1 Receptor Drugs in Colorectal Cancer. Issue 21 (3rd October 2021) - Shi, Yue; Wang, Xi; Meng, Yueming; Ma, Junjie; Zhang, Qiyu; Shao, Gang; Wang, Lingfei; Cheng, Xurui; Hong, Xiangyu; Wang, Yong; Yan, Zhibin; Cao, Yihai; et al.
Abstract: The neurokinin‐1 receptor (NK‐1R) antagonists are approved as treatment for chemotherapy‐associated nausea and vomiting in cancer patients. The emerging role of the substance P‐NK‐1R system in oncogenesis raises the possibility of repurposing well‐tolerated NK‐1R antagonists for cancer treatment. This study reports that human colorectal cancer (CRC) patients with high NK‐1R expression have poor survival, and NK‐1R antagonists SR140333 and aprepitant induce apoptotic cell death in CRC cells and inhibit CRC xenograft growth. This cytotoxicity induced by treatment with NK‐1R antagonists is mediated by induction of endoplasmic reticulum (ER) stress. ER stress triggers calcium release, resulting in the suppression of prosurvival extracellular signal‐regulated kinase (ERK)‐c‐Myc signaling. Along with ER calcium release, one ER stress pathway mediated by protein kinase RNA‐like ER kinase (PERK) is specifically activated, leading to increased expression of proapoptotic C/EBP‐homologous protein (CHOP). Moreover, NK‐1R antagonists enhance the efficacy of chemotherapy by increasing the sensitivity and overcoming resistance to 5‐fluorouracil in CRC cells through the induction of sustained ER stress and the consequent suppression of ERK‐c‐Myc signaling both in vitro and in vivo. Collectively, the findings provide novel mechanistic insights into the efficacy of NK‐1R antagonists either as a single agent or in combination with chemotherapy for cancer treatment. Abstract : The neurokinin‐1 receptor antagonists are repurposed as a new treatment option for patients with colorectal cancer via activation of endoplasmic reticulum stress to induce apoptosis.